MANAJEMEN PENDIDIKAN TINGGI: BAGAIMANAKAH LEMBAGA PENDIDIKAN TINGGI BANGKIT DARI KRISIS DAN KETERPURUKAN? - Kurniawan, Ade (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2025)
Many universities are experiencing a managerial crisis that impacts declining academic quality, lecturer productivity, and institutional competitiveness nationally and globally. This crisis is generally caused by weak internal governance that cannot adapt to the dynamics of the times. This article aims to analyze the main causes of weak internal management in universities and their impact on the quality of institutions, as well as formulate how higher education institutions can rise from crises and downturns. This study uses a literature review method by systematically reviewing various scientific literature that discusses university governance, institutional crises, and management strategies. The study results show that rigid bureaucracy, weak academic leadership, and lack of technology utilization are the dominant factors causing the crisis. These three factors impact the decline of academic quality, lecturer productivity, institutional reputation, and institutional competitiveness. For universities to rise, the authors highlight the importance of a psychological approach in building institutional resilience, including crisis awareness, self-evaluation, external support, and learning from the successful practices of other institutions. This study recommends adaptive and sustainable managerial strategies to strengthen university governance